Assessment of inter-and intra-audiologist agreements on Auditory Brainstem Response (ABR) waves interpretation and ABR variability - Dzulkarnain, Ahmad Aidil Arafat; Che Azid, Nor Diyana (Malaysian Medical Association, 2014)
Aim of study: This study investigated the consistency in Auditory Brainstem Response (ABR) waveform evaluations between two audiologists (inter-audiologist agreement) and within each of the audiologist (intra-audiologist agreement). Methods: Two audiologists from one of the audiology clinics in Kuantan, Pahang, Malaysia were involved in this study. Both audiologists were required to identify and mark the presence of Waves I, III and V in 66 ABR waveforms. Over a one-month interval, each audiologist was required to carry out the same procedure on the same ABR waveforms. This process was continued until we had three separate reviews from each audiologist. Results: There was a high inter-audiologist ABR waveform identification agreement (over the range 81.71–89.77%), but a lower intra-audiologist ABR waveform identification agreement (over the range 50%–78%) for both audiologists. Our results also showed a high intra-audiologist ABR latency agreement within 0.2 ms (>90%), but a slightly lower inter-audiologist latency agreement (75–84%) within 0.2 ms. Conclusion: Our results support the need for the clinic to implement further strategies for improving the respective lower agreements and consistencies. These include conducting a continuous education program and using an objective algorithm to support their interpretations.